Who hunts lemurs and why they hunt them. (May 2016) - Borgerson, Cortni; McKean, Margaret A.; Sutherland, Michael R.; Godfrey, Laurie R.
Abstract: The main threats to lemurs are habitat loss and hunting. Conservation policies often assume that people will decrease lemur hunting if they understand government prohibitions on hunting, are educated and/or involved in ecotourism, have access to affordable meat, and/or are healthy and financially secure. Yet these assumptions are often not well tested where conservation policies are implemented. We interviewed every member of a focal village in one of the most biodiverse places on earth, the Masoala peninsula of Madagascar. The factors that best predicted the decision to hunt lemurs were poverty, poor health, and child malnutrition. Knowledge of laws, level of education, involvement in ecotourism, traditional cultural values, taste preferences, opportunity, and human–wildlife conflict had no impact on lemur hunting. Our results suggest that the welfare of humans and lemurs are linked. The key to discouraging illegal hunting and improving the viability of Endangered lemur populations may be improving rural human health and welfare. Graphical abstract: Highlights: Developing sound lemur conservation policy requires knowing why lemurs are hunted. We test eleven popular hypotheses purporting to explain illegal hunting of lemurs. High education, knowledge of laws, and ecotourism do not reduce illegal hunting. Poverty, poor health, and child malnutrition best predict lemur hunting. Improving human health and welfare may be the key to discouraging illegal hunting.